2011
DOI: 10.1007/s10661-011-2045-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment due to intake of heavy metals through the ingestion of groundwater around two proposed uranium mining areas in Jharkhand, India

Abstract: Heavy metal pollution of water resources can be apprehended in East Singhbhum region which is a highly mineralised zone with extensive mining of copper, uranium and other minerals. Ten groundwater samples were collected from each site and the heavy metal analysis was done by atomic absorption spectrophotometer. Analysis of the results of the study reveals that the concentration of iron, manganese, zinc, lead, copper and nickel in groundwater of Bagjata mining area ranged 0.06-5.3 mg l(-1), 0.01-1.3 mg l(-1), 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…These results were in agreement with (Giri et al, 2012) studied the hazard quotient (HQ) for risk assessment due to intake of heavy metals through the ingestion of groundwater on ten groundwater samples collected from each sit Bagjata and Banduhurang area, India taking into account average water consumption of 1.48 m3 year −1 by an Indian adult. The HQs of all the considered heavy metals were below the threshold value of 1 as suggested by (USEPA, 1993).…”
supporting
confidence: 84%
“…These results were in agreement with (Giri et al, 2012) studied the hazard quotient (HQ) for risk assessment due to intake of heavy metals through the ingestion of groundwater on ten groundwater samples collected from each sit Bagjata and Banduhurang area, India taking into account average water consumption of 1.48 m3 year −1 by an Indian adult. The HQs of all the considered heavy metals were below the threshold value of 1 as suggested by (USEPA, 1993).…”
supporting
confidence: 84%
“…There is a growing concern over the metal pollution of the environmental components of Subarnarekha River Basin. The intense industrialization of the basin has also been a major contributor of certain metals to the water and sediment of the river basin (Upadhyay et al 2006;Giri et al 2012Giri et al , 2013Giri and Singh 2014). The studies also indicate that the metal pollution is more pronounced in the pre-monsoon season.…”
Section: Introductionmentioning
confidence: 92%
“…Giri et al (2010) have assessed the concentration of heavy metals (Fe, Mn, Zn, Pb, Cu, and Ni) in the groundwater of East Singhbhum region and found that Fe and Mn concentrations were higher than permissible limit. Health risks due to intake of heavy metals through the ingestion of groundwater around uranium mining areas in Jharkhand were also reported by Giri et al (2012).…”
Section: Introductionmentioning
confidence: 95%